Voxel-based full-field eigenstrain reconstruction of residual stresses in additive manufacturing parts using height digital image correlation - Uzun, F; Basoalto, H; Liogas, K; Chen, J; Dolbnya, IP; Wang, ZI; Korsunsky, AM (Elsevier, 2023)
The formation of residual stresses is inevitable during the additive manufacturing of metallic parts due to thermo-mechanicals effects, but the chaotic nature of printing processes makes it impossible to have a comprehensive understanding about the magnitude and distribution of these residuals. The voxel-based eigenstrain (inherent strain) reconstruction method is capable of the full-field reconstruction of residual stresses in discontinuous processing bodies at a scale that depends on the resolution of experimental data without using simplifying assumptions and regularisation functions. This advanced method firstly maps the distribution of eigenstrains and then quantifies corresponding residual stresses, residual elastic strains, and displacements by a cost-effective linear elastic computational framework. The reliability of this process solely depends on the quality of experimental data and the availability of computational power. The motivation behind this study is the use of the voxel-based eigenstrain reconstruction method for the full-field mapping of complex residual stress fields, that cannot be predicted by regularizing assumptions, in discontinuous processing additive manufacturing parts. The height Digital Image Correlation (hDIC) technique satisfied the need for high-quality experimental data by calculating triaxial displacements, corresponding to the elastic response of CM 247 LC powder bed fusion (PBF) additive manufacturing part after changes in the boundary conditions due to separation from the base, using optical profilometry measurements at a resolution adjusted in a way to reconstruct Type I residual stresses. Three components of displacements calculated by the hDIC were used to map the distribution of three components of eigenstrains for the reconstruction of six residual stress, six residual elastic strain and three displacement components that belong to the before and after separating from the base states. The reliability of calculations has been validated by monochromatic synchrotron X-ray beams in powder diffraction mode from the same surface of optical profilometry measurements and in transmission mode from the sampling volumes.